Prevalensi Gangguan Tidur Pada Anak Usia Prasekolah di Kecamatan Kuningan - Salma Nur Aullya; Adelse Prima Mulya; Nenden Nur Asriyani Maryam (Universitas Malahayati Lampung, 2026)
ABSTRACT The preschool period is an important developmental stage that requires adequate sleep to support physical growth, cognitive development, and emotional regulation in children. However, previous studies have shown that sleep disturbances among preschool children remain relatively high and may be influenced by environmental factors and pre-sleep habits. This study aimed to describe the sleep patterns of preschool-aged children in Kuningan District. A quantitative study with a descriptive approach was conducted. The sample consisted of 211 parents or guardians of kindergarten children who were selected using a proportionate stratified random sampling technique. Data were collected using the Indonesian version of the Children’s Sleep Habits Questionnaire (CSHQ) based on parental reports during the past week and were analyzed using univariate analysis. The results showed that the majority of children (86.7%) met the criteria for sleep disturbance based on a CSHQ score 41. Nevertheless, most children had a conducive sleep environment (70.6%), while the use of gadgets before bedtime was most frequently reported in the occasional category (49.3%). The average bedtime was 20.34, with a total sleep duration of approximately 10 hours within a 24-hour period. It can be concluded that most preschool children met the criteria for sleep disturbance despite having a relatively conducive sleep environment and sleep duration that remained within the recommended range. These findings highlight the importance of parental attention and the role of health professionals in promoting healthy sleep habits to support optimal sleep quality in children. Keywords: Preschool Children, Sleep Patterns, Sleep Disturbance. ABSTRAK Masa prasekolah merupakan periode perkembangan penting yang memerlukan pemenuhan kebutuhan tidur yang adekuat untuk mendukung pertumbuhan fisik, perkembangan kognitif, serta regulasi emosi anak. Namun, berbagai penelitian menunjukkan bahwa gangguan tidur pada anak prasekolah masih cukup tinggi dan dapat dipengaruhi oleh faktor lingkungan serta kebiasaan sebelum tidur. Penelitian ini bertujuan untuk menggambarkan pola tidur anak usia prasekolah di Kecamatan Kuningan. Penelitian ini menggunakan desain kuantitatif dengan pendekatan deskriptif. Sampel penelitian berjumlah 211 orang tua atau wali anak taman kanak-kanak yang dipilih menggunakan teknik proportionate stratified random sampling. Data dikumpulkan menggunakan kuesioner Children’s Sleep Habits Questionnaire (CSHQ) versi Indonesia berdasarkan laporan orang tua selama satu minggu terakhir dan dianalisis secara univariat. Hasil penelitian menunjukkan bahwa sebagian besar anak (86,7%) memenuhi kriteria gangguan tidur berdasarkan skor CSHQ 41. Meskipun demikian, sebagian besar anak memiliki lingkungan tidur yang kondusif (70,6%), sementara penggunaan gadget sebelum tidur paling banyak berada pada kategori kadang-kadang (49,3%). Rata-rata waktu tidur malam anak adalah pukul 20.34, dengan total durasi tidur sekitar 10 jam dalam 24 jam. Penelitian ini menyimpulkan bahwa sebagian besar anak prasekolah memenuhi kriteria gangguan tidur meskipun memiliki lingkungan tidur yang relatif kondusif dan durasi tidur yang masih berada dalam kisaran rekomendasi. Temuan ini menunjukkan pentingnya perhatian orang tua dan tenaga kesehatan terhadap kebiasaan tidur anak guna mendukung kualitas tidur yang optimal. Kata Kunci: Anak Prasekolah, Pola Tidur, Gangguan Tidur.